A Study of Actual Training Time Administration in Bedra Specialized Weightlifting Club - Hussein, Hussein Khmais (Journal of Physical Education, 2021)
The researcher, through his work as a coach in some Iraqi weightlifting clubs, noticed hesitation in time administration during training sessions of clubs and league. He noticed that so much time is spend on details not related to the training program thus, he aimed at identifying the variables of the research through designing data registration form that includes all these variables (delays like wearing Band-Aids, drinking water, starting time after coach’s whistle, exercises timing and, moving from one exercise to the other). A comparison was made between two different training administrations after the first beginning procedures, after it, and during two different times. The results showed significant differences between the two administrations in time investment in favor of the training procedure.